2012
DOI: 10.5352/jls.2012.22.10.1324
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Acids on In Vitro Ruminal Fermentation Characteristics and Methane Emission

Abstract: The objective of this study was to evaluate the in vitro effects of organic acids on methane emission and ruminal fermentation characteristics. We expected our methodology to result in a decrease of methanogens attached to the surface of rumen ciliate protozoa by addition of organic acids and in particular a decrease in methane emission. A fistulated Holstein cow of 650 kg body weight was used as a donor of rumen fluid. Organic acids (aspartic acid, fumaric acid, lactic acid, malic acid, and succinic acid) kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(17 reference statements)
2
0
0
Order By: Relevance
“…In the present study, only 0.1% and 0.3% dose of FA increased protozoa counts numerically and MA showed a reducing effect on protozoa counts with increasing dose. This finding is consistent with the reports of other studies (17,27,32) investigating the effects of organic acids on rumen microorganisms. Ok et al (27) reported that FA and MA have different effects on bacteria, protozoa and other microbial community.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, only 0.1% and 0.3% dose of FA increased protozoa counts numerically and MA showed a reducing effect on protozoa counts with increasing dose. This finding is consistent with the reports of other studies (17,27,32) investigating the effects of organic acids on rumen microorganisms. Ok et al (27) reported that FA and MA have different effects on bacteria, protozoa and other microbial community.…”
Section: Resultssupporting
confidence: 94%
“…This finding is consistent with the reports of other studies (17,27,32) investigating the effects of organic acids on rumen microorganisms. Ok et al (27) reported that FA and MA have different effects on bacteria, protozoa and other microbial community. They reported that these acids had an increasing effect on rumen bacteria, but decreased the number of methanogenic archaea species that could form complexes with protozoa.…”
Section: Resultssupporting
confidence: 94%